Implikasi Yuridis Penyelesaian Sengketa Wanprestasi melalui Mekanisme Non-Litigasi terhadap Kepastian Hukum dan Kekuatan Eksekutorial di Indonesia - Chalisa Raniah Idrus; Alifah Kahillah Almaira; Najwa Sabrina; Mesya Assauma Nurfitrah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Resolving default disputes through non-litigation mechanisms is gaining popularity in Indonesia due to its time and cost efficiency compared to litigation. However, its implementation still faces challenges related to legal certainty and the enforceability of decisions. This study examines two main issues: first, the legal implications of resolving default claims through non-litigation mechanisms for the legal protection of the parties; and second, the enforceability of arbitration decisions in the Indonesian civil procedural law system. The research method used is normative juridical with a statutory and conceptual approach. Primary legal materials include the Civil Code and Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, while secondary legal materials come from legal literature and scholarly journals. The results show that resolving default disputes through arbitration provides legal protection by strengthening the principles of freedom of contract and due process of law, but still leaves behind the problem of high costs and limited corrective legal remedies. Arbitration awards have the same enforceable power as court decisions after being registered with the district court and issued by the chief justice. However, the effectiveness of enforcement remains hampered by broad interpretations of the concept of public order and resistance from the losing party. This study concludes that although arbitration awards are recognized as having enforceable power, their successful implementation depends heavily on the harmony between arbitration institutions and general courts, as well as the good faith of the parties.